2016
DOI: 10.1177/1359105316633285
|View full text |Cite
|
Sign up to set email alerts
|

The caregiver burden in male romantic partners of women with non-metastatic breast cancer: The protective role of couple satisfaction

Abstract: We examined the evolution of the subjective burden of romantic partners caring for women with non-metastatic breast cancer and investigated the moderating role of couple satisfaction on caring stress. Forty-seven partners filled out questionnaires 3 and 12 months after surgery. Using a stress process model, we examined caring stressors and moderating factors (couple satisfaction, coping and social support) as predictors of subjective burden. Results showed that subjective burden decreases over time and that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…In other words, it is thought that relationship satisfaction protects individuals from experiencing stress in the first place or that relationship satisfaction helps people cope effectively when they do experience stress, with stress proximally related to physical health outcomes. In the case of spousal caregivers, studies that primarily focus on caregiver outcomes show that caregivers who report greater pre-illness and current relationship satisfaction experience greater burden, depressive symptoms, and potentially harmful behaviors toward their care recipient (Cairo Notari et al, 2016; Quinn et al, 2009; Steadman et al, 2007; Williamson and Shaffer, 2001). Relatedly, it has been shown that when both caregivers and care recipients feel more compassionate love for one another, caregivers report less burden and more positive aspects of caregiving (Monin et al, 2014b).…”
Section: Associations Between Health and Relationship Satisfaction Inmentioning
confidence: 99%
“…In other words, it is thought that relationship satisfaction protects individuals from experiencing stress in the first place or that relationship satisfaction helps people cope effectively when they do experience stress, with stress proximally related to physical health outcomes. In the case of spousal caregivers, studies that primarily focus on caregiver outcomes show that caregivers who report greater pre-illness and current relationship satisfaction experience greater burden, depressive symptoms, and potentially harmful behaviors toward their care recipient (Cairo Notari et al, 2016; Quinn et al, 2009; Steadman et al, 2007; Williamson and Shaffer, 2001). Relatedly, it has been shown that when both caregivers and care recipients feel more compassionate love for one another, caregivers report less burden and more positive aspects of caregiving (Monin et al, 2014b).…”
Section: Associations Between Health and Relationship Satisfaction Inmentioning
confidence: 99%
“…As defined by the Systemic‐Transactional Model (STM), distress affects both partners directly and indirectly because of their interdependence . Furthermore, the illness negatively affects not only patients (eg, fatigue, insomnia, and psychological distress) but also their partners, who experience significant caregiver burden . Therefore, BC can be understood as a shared stressor.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, partners have to face a highly challenging situation. On the one hand, they find themselves in the role of an ‘informal caregiver’, with the duties of helping the women and taking over some (if not all) household chores; on the other hand, they have to cope with their own stress and fear of losing their loved ones (Cairo Notari, Favez, Notari, Charvoz, & Delaloye, ; Stenberg, Ruland, & Miaskowski, ; Wagner, Tanmoy Das, Bigatti, & Storniolo, ). A supporting couple relationship, at the emotional and instrumental levels, is a major factor of resilience in these situations (Giese‐Davis, Hermanson, Koopman, Weibel, & Spiegel, ; Manne et al ., ).…”
Section: Introductionmentioning
confidence: 99%